Moments-based parametric sensitivity analysis of X-parameters - Kassis, Marco T. (2019)
The polyharmonic distortion parameters of a nonlinear structure or circuit block, often referred to as X-parameters (X-parameters is a registered trademark of Agilent Technologies) relate the different harmonics of the incident waves to those of the reflected waves in the frequency domain. Recently, a closed-form derivative-based approach for calculating the X-parameters' sensitivity with respect to linear circuit elements has been developed for a given input amplitude level. In this article, we build on those results and present an efficient and accurate moment-based method for the sensitivity analysis with respect to both linear and nonlinear circuit parameters, parameterized with respect to the input amplitude. The proposed method allows for the accurate and efficient computation of Xparameter sensitivity terms without the need for CPU expensive sweeps or brute force perturbation.